2007
DOI: 10.1007/s11267-006-9094-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Supply on the Sensitivity to O3 of Growth and Photosynthesis of Japanese Beech (Fagus crenata) Seedlings

Abstract: To obtain basic information for evaluating critical levels of O 3 under different nitrogen loads for protecting Japanese beech forests, two-year-old seedlings of Fagus crenata Blume were grown in potted andisol supplied with N as NH 4 NO 3 solution at 0, 20 or 50 kg ha −1 year −1 and exposed to charcoal-filtered air or O 3 at 1.0, 1.5 and 2.0 times the ambient concentration from 16 April to 22 September 2004. The O 3 induced significant reductions in the wholeplant dry mass, net photosynthetic rate at 380 μmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…when the sensitivity of the net photosynthetic rate to O3 was increased by the N load, the negative impact of O3 on the whole-plant dry mass was increased (Watanabe et al,. 2007;Yamaguchi et al, 2007a;Yamaguchi et al, 2007b). In C. sieboldii seedlings, however, the sensitivity of the whole-plant dry mass to O3 did not necessarily correspond to that of the net photosynthetic rate to O3 (Tables 4 and 5).…”
Section: Growth and Photosynthetic Responses To Ozone And Nitrogen Loadsmentioning
confidence: 96%
“…when the sensitivity of the net photosynthetic rate to O3 was increased by the N load, the negative impact of O3 on the whole-plant dry mass was increased (Watanabe et al,. 2007;Yamaguchi et al, 2007a;Yamaguchi et al, 2007b). In C. sieboldii seedlings, however, the sensitivity of the whole-plant dry mass to O3 did not necessarily correspond to that of the net photosynthetic rate to O3 (Tables 4 and 5).…”
Section: Growth and Photosynthetic Responses To Ozone And Nitrogen Loadsmentioning
confidence: 96%
“…It was also reported that the exposure to O 3 reduced the net photosynthetic rate of the leaves or needles of Japanese white birch, Japanese red pine, Japanese larch, Q. serrata and C. sieboldii (Watanabe et al, 2008(Watanabe et al, , 2007(Watanabe et al, , 2006Nakaji et al, 2004;Nakaji and Izuta, 2001;Matsumura et al, 1998). When net photosynthetic rate was reduced by the exposure to O 3 , simultaneous reductions in the carboxylation efficiency (CE), CO 2 -saturated net photosynthetic rate (A max ) and/or maximum quantum yield of photosystem (PS) II (F v /F m ), and increase in the stomatal diffusive conductance to water vapor (g s ) in the leaves or needles of Japanese forest tree species were also observed (Yamaguchi et al, 2007a;Watanabe et al, 2005;Nakaji and Izuta, 70 Asian Journal of Atmospheric Environment, Vol. 5(2), 65-78, 2011 2001; Yonekura et al, 2001a, b;Matsumura et al, 1998Matsumura et al, , 1996Izuta et al, 1996).…”
Section: Yrmentioning
confidence: 99%
“…Regarding the higher Al(RE) observed under eO3 in beech, the possible explanation is similar to that discussed above for birch. However, the O3-induced reduction of Al concentration in older leaves of beech (Hoshika et al 2013b, Yamaguchi et al 2007) may not be adequately counterbalanced by the increase in foliar Al during leaf senescence in plants growing on acidic soils (Gjengedal 1996), and this may explain the increase of (Al)RE in the treatment EV observed in this study (Tab. 2).…”
Section: Beech Seedlingsmentioning
confidence: 76%
“…This is especially important for plants grown in poor fertility soils like S soil in this study. Yamaguchi et al (2007) reported that the sensitivity of growth and photosynthetic parameters to O3 in beech became high at higher concentrations of N in the soil. Moreover, Hoshika et al (2013b) concluded that late leaves in birch were more susceptible to O3 stress.…”
Section: Beech Seedlingsmentioning
confidence: 99%
See 1 more Smart Citation